2008
DOI: 10.1177/1933719108322432
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Angiotensin II Generation Induced by Placenta-derived Factors From Preeclampsia

Abstract: Hypersensitivity to angiotensin II contributes to the increased vasoconstriction in preeclampsia. In this study, we determined whether placenta-derived factors could affect endothelial cell angiotensin II generation. Our results showed that more angiotensin II was produced by endothelial cells treated with preeclampsia placental conditioned medium than the cells treated with normal conditioned medium or untreated controls. To determine which pathway, angiotensin-converting enzyme or nonangiotensin-converting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This may imply that there is no quantitative increase in vasopressors, but rather an increase in sensitivity to the existing quantity of vasoactive factors present in pre-eclamptic women. Our study provides proof of this by showing elevated expression of the AT1 receptors in late-onset pre-eclamptic patients compared to the normotensive controls, chronic hypertensive and early-onset pre-eclamptic groups, thereby accounting for the heightened sensitivity to the powerful vasoconstrictor angiotensin II, which is in accordance with previous studies 52,53…”
Section: Discussionsupporting
confidence: 92%
“…This may imply that there is no quantitative increase in vasopressors, but rather an increase in sensitivity to the existing quantity of vasoactive factors present in pre-eclamptic women. Our study provides proof of this by showing elevated expression of the AT1 receptors in late-onset pre-eclamptic patients compared to the normotensive controls, chronic hypertensive and early-onset pre-eclamptic groups, thereby accounting for the heightened sensitivity to the powerful vasoconstrictor angiotensin II, which is in accordance with previous studies 52,53…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, Ang I may be converted to Ang II through the action of chymase, by an ACE independent pathway [21]. Chymase is expressed in the human placenta, its activity is increased in placentae from women with preeclampsia [22], and it may increase Ang II production [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, the patients may show a series of manifestations, such as high blood pressure and proteinuria. 23,24 As a vasoactive substance reacting with its specific receptors (AdipoR1 and AdipoR2), adiponectin has important physiological roles, such as protecting vascular endothelial cells, increasing insulin sensitivity, inhibiting inflammation and inhibiting atherosclerosis. By measuring plasma adiponectin in 1842 pregnant women in early pregnancy and tracking the outcomes of their pregnancies, D'Anna et al 4 found that plasma adiponectin in patients with preeclampsia was lower than in pregnancy-induced hypertension patients and normal patients.…”
Section: Discussionmentioning
confidence: 99%